Cardiac vagal control mediates the relation between past depression and blood pressure several years later among young adults - Yang, Xiao; Daches, Shimrit; Yaroslavsky, Ilya; George, Charles J.; Kovacs, Maria (Psychophysiology, 2020)
Depression has been associated with high blood pressure (BP). However, the mechanisms of the relation between depression and high BP are unclear. We therefore examined whether impaired cardiac vagal control, indexed as low levels of resting respiratory sinus arrhythmia (RSA), serves as a route from depression to high BP. The sample included 125 subjects with histories of depression (probands), 123 never depressed siblings of probands (high‐risk siblings), and 156 controls. Resting RSA was assessed at Time 1 (T1) along with BP when subjects were adolescents (Mage = 16.3 years); systolic and diastolic BP (SBP and DBP) were measured again at Time 2 (T2) when subjects were young adults (Mage = 22.3 years). Linear mixed‐effects models were used to examine the group differences in resting RSA and T2 BP outcomes and to test for RSA mediation of the relation between depression (history or being at high risk) and BP. Resting RSA was lower among probands than controls but was similar among high‐risk siblings and controls, while the subject groups did not differ in T2 SBP or DBP. Controlling for T1 BP, depression history indirectly affected T2 DBP (but not SBP) through resting RSA. The findings suggest that, although the direct detrimental effects of depression on BP are not yet evident in young adulthood, among those with depression histories, impaired cardiac vagal control appears to serve as a mechanism of elevated DBP. Depression is associated with hypertension but the mechanism of the association is unclear. Our study is the first to report that impaired cardiac vagal control is a pathway from depression history to hypertension. Therefore, screening for low respiratory sinus arrythmia may facilitate early identification of individuals at high risk for hypertension.